Copper micro and nano particles mixture for 3D interconnection application - Dai, Yuan-Yuan (2016)
Copper is a well-known material used for interconnections application. It offers economical advantage over silver and has high electrical conductivity. Studies on copper nano-paste (comprising of monodispersed nano-particles) application on surfaces have reported cracking and a low packing density with high porosity. A novel method utilizing a mixture of copper micron sized particles and nano-particles paste is proposed and investigated. This enables high packing density with low resistivity thus improving the interconnection for low temperature electronics packaging. A model to find the optimum micro-nano particle size ratio is established to achieve high packing density. The algorithm is based on Monte Carlo method. Firstly, the large micro-particles are arranged in Face-Centered-Cubic (FCC) structure. Next, a fixed initial number of smaller spheres (nano-particles) are randomly arranged in the interstitial spaces between the micro- particles. A stepwise increment in nano-particle diameter at a fixed micro-particle size (1 µm) is carried out until the system reaches a jammed state. Based on the modeling results, a weight ratio of 6.3:1 between micro- and nano- copper particles is predicted to provide maximum packing. Further experiments were carried out to examine the properties of the mixed, micro- and nanopastes. The particles were firstly dispersed in low boiling point organic solvents which are able to evaporate at low temperature. Afterwards, the three kinds of pastes were inspected under microscope and SEM images and it is found that the nano-paste has small cracks. To solve the paste adhesion issue and improve paste performance a new recipe is developed. A washing procedure to remove the surface oxide on the micro-particles before making the paste and a method to improve mixture uniformity are developed. Next, Thermal Gravimetric Analysis (TGA) was carried out to investigate the pastes thermal property. The mixed paste shows a transitional temperature of ~201 °C, which is lower than reference micro- and nano- paste respectively. In-situ temperature and resistance measurements show that mixed paste made by new recipe has lower electrical resistance. After sintering, the mixed paste shows 1.0 Ω of resistance whereas the micro-paste shows 2.3 Ω of resistance. The resistance of nano-paste initially decreases to 1.8 Ω then it shows a rapid increase during sintering due to cracks. Besides, packing density of mixed pastes with different ratios was studied and analyzed using Scanning Electron Microscopy (SEM) and ImageJ software. The 3:1 mixed paste has lowest porosity and no cracks were observed. The result is also verified by sheet resistance measurement that the 3:1 mixed paste shows only 0.3 Ω/sq as compared to micro-paste which is 3 Ω/sq. The deviation between simulation and experiments is possibly because the nano-particles are not always arranged around micro-particles as expected. As a final application, die to wafer bonding has been conducted by using the three types of paste and the bond strength is characterized by shear bond test. Results show that the mixed paste has higher bond strength of 0.7 MPa than micro- and nano- paste of 0.5 MPa and 0.1 MPa respectively after bonding at 200 °C without pressure. Therefore, this technique could be used in future applications such as low temperature metal-metal bonding for 3D interconnects application.